Evaluation of a Custom SNP Panel for Identifying and Rectifying of Misjudged Paternity in Deficiency Cases - Chang, Liao; Yu, Huiyun; Miao, Xinyao; Wen, Siqi; Zhang, Bao; Li, Shengbin (Frontiers in Genetics, 2021)
Parentage testing is routinely performed by genotyping short tandem repeat (STR) through capillary electrophoresis in present. However, ambiguous or even misjudged paternity based on STRs happens from time to time in cases where only one putative parent is available. We analysed STR data of 7,818,969 unrelated pairs and 75 close-relative pairs, and found that although the probability of a random false match between nonrelatives was 4.22×10-6, the incidence of false or ambiguous paternity results between children and first-degree relatives of their true parent was as high as 18.67%. These results highlight the risk of false inclusion of a relative or even nonrelatives in parentage testing with STRs. We then validated all ambiguous STR results by targeted sequencing with a custom panel containing 4,830 individual identification SNP (IISNP), found that the ratio of mismatch loci to total SNPs was 1.78-6.95% in close relatives compared with 10.93-13.49% in unrelated pairs. Last, we reported 3 real cases with undetermined paternity by STRs, and rectify them by dissecting with our IISNP panel. These results suggested that high-density IISNP panel can be used to identify and rectify misjudged cases effectively.